Zerumbone from Zingiber zerumbet (L.) smith: a potential prophylactic and therapeutic agent against the cariogenic bacterium Streptococcus mutans - Thiago Moreira da Silva; Carlos Danniel Pinheiro; Patricia Puccinelli Orlandi; Carlos Cleomir Pinheiro; Gemilson Soares Pontes (BMC Complementary and Alternative Medicine, 2018)
Abstract Background Essential oil obtained from rhizomes of the Zingiber zerumbet (L.) Smith (popularly known in Brazil as bitter ginger) is mainly constituted by the biomolecule zerumbone, which exhibit untapped antimicrobial potential. The aim of this study was to investigate the antimicrobial activity of the zerumbone from bitter ginger rhizomes against the cariogenic agent Streptococcus mutans. Methods Firstly, the essential oil from rhizomes of Zingiber zerumbet (L.) Smith extracted by hydrodistillation was submitted to purification and recrystallization process to obtain the zerumbone compound. The purity of zerumbone was determined through high-performance liquid chromatography analysis. Different concentrations of zerumbone were tested against the standard strain S. mutans (ATCC 35668) by using microdilution method. The speed of cidal activity was determined through a time kill-curve assay. The biological cytotoxicity activity of zerumbone was assessed using Vero cell line through MTT assay. Results The zerumbone showed a minimum inhibitory concentration (MIC) of 250 μg/mL and a minimum bactericidal concentration (MBC) of 500 μg/mL against S. mutans. After six hours of bacteria-zerumbone interaction, all concentrations tested starts to kill the bacteria and all bacteria were killed between 48 and 72 h period at the concentration of 500 μg/mL (99,99% of bacteria were killed in comparison with original inoculum). In addition, zerumbone showed no cytotoxicity activity on mammalian continuous cells line. Conclusions These results draw attention to the potential of zerumbone as antimicrobial agent against S. mutans infection, indicating its possible use in the phyto-pharmaceutical formulations as new approach to prevent and treat tooth decay disease.